ENT 530 Social Media Portfolio: Ready Mixed Sauce and Sambal by Food Tree Factory / Muhammad 'Aqil Muaz Azman - Azman, Muhammad 'Aqil Muaz (2021)
Ready Mixed Sauce and Sambal by Food Tree Factory is a special homemade recipes product found by Mrs. Refqah with support by her husband Mr. Ikhman. Ready Mixed Sauce and Sambal is easy to cook product which have three types namely, Creamy Butter Sauce, Black Magic Sauce, and Balado Berapi Sambal. Food Tree Factory is located at Denai Alam, Shah Alam, Selangor. Facebook Page is a social media platform that have been choose for social media portfolio to completing task by Madam Salzainna Zainul Abidin. The objective of this project is to study and experiences the real entrepreneurial business. Through this Facebook platform we need to creating Facebook page, teaser post, creating copywriting hard sell and soft sell. I have choice this product for my social media portfolio which is Facebook page and use Ready Mixed Sauce and Sambal by Food Tree Factory as the social media page name. My role and tasks for Food Tree Factory product is as dropshipping. Ready Mixed Sauce and Sambal by Food Tree Factory is targeting people who love homemade and versatile sauce recipes. Through this social media platform, I have gather knowledge and learn how to post content in Facebook page for business product whether teaser, soft sell, and hard sell. I also learn how to attract audience through copywriting.